The art of multiprocessor programming. - Herlihy, Maurice, ....-; Shavit, Nir, ....- (Amsterdam : Elsevier, 2008)
As the computer industry changes from single-processor to multiprocessor architectures, this revolution requires a fundamental change in how programs are written. To leverage the performance and power of multiprocessor programming, also known as multicore programming, you need to learn the new principles, algorithms, and tools presented in this book. It includes fully-developed Java examples detailing data structures, synchronization techniques, transactional memory, and more.